Modern mechanisms for developing students' language skills through ICT in classroom and extracurricular English classes - Tukhtaboyeva, Mahliyo (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Integrative learning content is one of the main mechanisms of the CIL technology. Integration is a complex pedagogical approach that involves the formation of educational content by organically linking scientific and linguistic knowledge. When developing integrative learning content, there are a number of important principles and principles of planning the educational process, the correct application of which ensures the effectiveness of this technology.